2021
DOI: 10.1146/annurev-arplant-081720-010120
|View full text |Cite
|
Sign up to set email alerts
|

Advances and Opportunities in Single-Cell Transcriptomics for Plant Research

Abstract: Single-cell approaches are quickly changing our view on biological systems by increasing the spatiotemporal resolution of our analyses to the level of the individual cell. The field of plant biology has fully embraced single-cell transcriptomics and is rapidly expanding the portfolio of available technologies and applications. In this review, we give an overview of the main advances in plant single-cell transcriptomics over the past few years and provide the reader with an accessible guideline covering all ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
93
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(94 citation statements)
references
References 103 publications
0
93
0
1
Order By: Relevance
“…The plates were incubated for 24h at 37°C. Antagonistic activity was estimated by identifying zones of inhibited growth ( Seyfferth et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…The plates were incubated for 24h at 37°C. Antagonistic activity was estimated by identifying zones of inhibited growth ( Seyfferth et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…This issue can otherwise be assessed with pipelines such as Doublet Finder and Scrublet [43,44] (Figure 2). While data quality control and analysis pipelines for plant scRNA-Seq studies are now being discussed (e.g., [29,30]), this requires further work and is complicated by the metazoan-tailored tools commonly used. For example, a better understanding of mRNA content across plant cells in a given tissue would mean that cell-calling thresholds based on UMIs can be positioned more accurately.…”
Section: Balancing Sequencing Reads Against Cell Numbersmentioning
confidence: 99%
“…Principal among these are guaranteeing a viable cell selection, dealing with noise resulting from cell-isolation procedures, accommodating biotic/abiotic stress responses in this context, and interpreting the 'cluster cloud' and the detailed information inherent, beyond just coarse identification of cell types. There are many fine reviews that detail the state-of-the-art technology and data analysis methods, for example, [25][26][27][28], and several that focus specifically on plant applications, for example, [29,30]. However, undertaking an experiment of this nature on a plant tissue requires navigating some novel practical issues.…”
mentioning
confidence: 99%
“…To overcome this resolution barrier, single-cell transcriptomics was developed. A glance at the papers about using the single-cell transcriptomics in plant science showed that it became very popular (see Table S1) and is widely discussed technology today [126,[188][189][190]. Several groups undertook the first attempts for single-cell transcriptome assessment in 2013 [191] and 2015-2016 [192,193].…”
Section: Single-cell Transcriptomicsmentioning
confidence: 99%